Grenada : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1997)
This paper reports economic developments in Grenada during the 1990s. Following a strong expansion over 1987-91, real GDP grew at a slower pace in 1992 and declined in 1993, largely reflecting the adoption of adjustment measures and a severe drought. Growth resumed in 1994 owing to stronger tourism and manufacturing activity, the installation of new electricity-generating capacity, and increased output by the water company. In 1995, real GDP continued to expand at an annual rate of about 3 percent, mainly because of a recovery in agricultural output induced by higher export prices.